Global forest fragmentation change from 2000 to 2020 - Ma, Jun; Li, Jiawei; Wu, Wanben; Liu, Jiajia (Nature communications, 2023)
A comprehensive quantification of global forest fragmentation is urgently required to guide forest protection, restoration and reforestation policies. Previous efforts focused on the static distribution patterns of forest remnants, potentially neglecting dynamic changes in forest landscapes. Here, we map global distribution of forest fragments and their temporal changes between 2000 and 2020. We find that forest landscapes in the tropics were relatively intact, yet these areas experienced the most severe fragmentation over the past two decades. In contrast, 75.1% of the world’s forests experienced a decrease in fragmentation, and forest fragmentation in most fragmented temperate and subtropical regions, mainly in northern Eurasia and South China, declined between 2000 and 2020. We also identify eight modes of fragmentation that indicate different recovery or degradation states. Our findings underscore the need to curb deforestation and increase connectivity among forest fragments, especially in tropical areas. Forest losses and gains are highly dynamic processes. Here, the authors present a forest fragmentation index to map distribution and temporal changes of forest fragments globally, revealing major trends and patterns during the first two decades of the 21st century.